2006
DOI: 10.1021/jp062405x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Spectroscopic, and Theoretical Investigations of Excited-State Proton Transfer in the Doubly Hydrogen-Bonded Dimer of 2-Butylamino-6-methyl-4-nitropyridine N-Oxide

Abstract: The crystal structure of 2-butylamino-6-methyl-4-nitropyridine N-oxide (2B6M) was resolved on the basis of X-ray diffraction. Solid 2B6M occurs in the form of a doubly hydrogen-bonded dimer with squarelike hydrogen-bonding network composed of two intra- (2.556(2) A) and two intermolecular (2.891(2) A) N-H...O type hydrogen bonds. The molecule thus has both a protonable and a deprotonable group that led us to investigate the possibility of an excited-state proton transfer (ESIPT) reaction in different solvents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…This process was estimated as a very fast one in polar solvents and described as being triggered by creation of the excited intramolecular CT state. From the other hand, in nonpolar medium such process was shown to be much slower [25,26]. An interesting conclusion was drawn out, namely, it was suggested that the observed excitation wavelength dependence of the quantum yield is due to existence of the two different intramolecular proton transfer processes [26].…”
Section: S-73mentioning
confidence: 97%
See 4 more Smart Citations
“…This process was estimated as a very fast one in polar solvents and described as being triggered by creation of the excited intramolecular CT state. From the other hand, in nonpolar medium such process was shown to be much slower [25,26]. An interesting conclusion was drawn out, namely, it was suggested that the observed excitation wavelength dependence of the quantum yield is due to existence of the two different intramolecular proton transfer processes [26].…”
Section: S-73mentioning
confidence: 97%
“…Some of EDA systems showing the dual fluorescence can be used in the fabrication of molecular switches [21]. The N-oxides molecules, under considerations, show the dual fluorescence, too [20,25,26].…”
Section: S-73mentioning
confidence: 99%
See 3 more Smart Citations